2001
DOI: 10.3758/cabn.1.3.239
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of imagined self-rotation

Abstract: In the present study, functional magnetic resonance imaging was used to examine the neural mechanisms involved in the imagined spatial transformation of one's body. The task required subjects to update the position of one of four external objects from memory after they had performed an imagined self-rotation to a new position. Activation in the rotation condition was compared with that in a control condition in which subjects located the positions of objects without imagining a change in selfposition. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 52 publications
8
53
1
Order By: Relevance
“…Whereas some earlier studies showed that mental imagery of body parts (such as arms and hands) predominantly activates left parietal cortex (Bonda et al 1995;Kosslyn et al 1998;Zacks et al 1999;Creem et al 2001;de Jong et al 2001) we found bilateral or bilateral and right predominant parietal activations for both types of body stimuli that were used in the present study. We suggest that mental imagery of symmetrical body stimuli (such as full or upper bodies used here) activate parietal cortex bilaterally whereas mental imagery of asymmetrical or lateralized body parts more strongly relies on left parietal cortex.…”
Section: Parietal Cortexcontrasting
confidence: 97%
See 2 more Smart Citations
“…Whereas some earlier studies showed that mental imagery of body parts (such as arms and hands) predominantly activates left parietal cortex (Bonda et al 1995;Kosslyn et al 1998;Zacks et al 1999;Creem et al 2001;de Jong et al 2001) we found bilateral or bilateral and right predominant parietal activations for both types of body stimuli that were used in the present study. We suggest that mental imagery of symmetrical body stimuli (such as full or upper bodies used here) activate parietal cortex bilaterally whereas mental imagery of asymmetrical or lateralized body parts more strongly relies on left parietal cortex.…”
Section: Parietal Cortexcontrasting
confidence: 97%
“…Both OBTtasks led to strong bilateral activation of parietal cortex. This is concordant with activations at this site observed in most studies investigating the neural correlates of mental imagery of bodily stimuli (Bonda et al 1995;Kosslyn et al 1998;Zacks et al 1999;Creem et al 2001;de Jong et al 2001;Lenggenhager et al 2006), but also non-corporeal objects (Pegna et al 1997;Harris and Miniussi 2003;Vingerhoets et al 2001;Alivisatos and Petrides 1997;Carpenter et al 1999;Kawamichi et al 2007).…”
Section: Parietal Cortexsupporting
confidence: 89%
See 1 more Smart Citation
“…The histograms show the mean response time in milliseconds ( §standard error to the mean, vertical bars) for the plant presented at 60° and 120°( averaged over clockwise and counterclockwise stimuli) for subjects using (a) an object-based versus (b) an egocentric mental transformation strategy These authors found that right anodal GVS involved a bilateral hemispheric activation of the superior temporal gyrus, posterior insula, anterior inferior parietal cortex, as well as right lateral occipito-parietal activation, whereas activations during left anodal GVS were conWned to the right hemisphere only (superior temporal gyrus, posterior insula, anterior inferior parietal cortex). As mental transformation has been shown to rely on bilateral parietal and temporooccipital activations (bodies: Zacks et al 1999;Creem et al 2001;Blanke et al 2005, objects: Kosslyn et al 1998Vingerhoets et al 2001), we speculate that bilateral activations due to right GVS interfere more strongly with bilateral activations during mental transformation in superior temporal gyrus, posterior insula, and inferior parietal cortex. Interference of right GVS at these sites might thus lead to the observed decrease in task performance.…”
Section: Diverences Between Right and Left Galvanic Vestibular Stimulmentioning
confidence: 72%
“…The exact anatomical location of these mental transformation processes is still controversial and seems to depend on additional variables such as sex, handedness, task diYculty and the control task (Kosslyn et al 1998;Jordan et al 2002). Nevertheless, as described in a meta-analysis by Zacks and Michelon (2005), object-based transformation would rely predominantly on unilateral right fronto-parietal cortex, while egocentric transformation would involve a more bilateral network (temporo-parieto-occipital junction; superior parietal lobule) with either right or left hemispheric predominance (Vallar et al 1999;Zacks et al 1999;Creem et al 2001;Vogeley and Fink 2003;Blanke et al 2005). Thus, the more bilateral cortical network activated by right GVS (see below) may interfere more strongly with mental transformation employing egocentric transformation.…”
Section: Inxuence Of the Mental Transformation Strategymentioning
confidence: 99%